33.3k views
3 votes
Below is the graph of y equals 3x translated to become the graph of y = 3x + 1 - 2

Below is the graph of y equals 3x translated to become the graph of y = 3x + 1 - 2-example-1
User Rion
by
4.2k points

1 Answer

5 votes

Step-by-step explanation:

If we have a function g(x) = f(x) - c, we can say that g(x) is f(x) shifted c units down.

If we have a funtion g(x) = f(x+c), we can say that g(x) is f(x) shifted c units to the left.

Therefore, the graph of y = 3^(x+1) - 2 is equal to the graph of y = 3^x shifted 2 units down and 1 unit to the left.

Answer:

So, the graph of the function is:

Below is the graph of y equals 3x translated to become the graph of y = 3x + 1 - 2-example-1
User Sharada
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.